Factors influencing the loyalty of employee in relation to organizational climate from an Islamic perspective - Abdul Ghani, Zurina; Hashim, Junaidah; Abdul Rahman, Rozailin (Springer Nature, 2016)
The main purpose of this paper is to understand the determinants of loyalty in relation to organizational climate from an Islamic perspective. The data were collected among the 172 Muslim managers and 509 Muslim employees in various industries, public and private sectors. The respondents of 172 Muslim managers are HR managers in particular. The study used measurement adopted from previous study. The implications of the study are discussed. Findings of this study could be used by HR practitioners and scholars in building management concerns and strategic plan for a better HRD systems and practices from the Islamic point of views